Judges’ intervention in witness examination as a cause of omissions in interpretation in the Hong Kong courtroom - Ng, Eva Nga Shan (International Journal of Speech, Language and the Law, 2015)
Research on court interpreting has by and large pointed to the court interpreters’ incompetence or otherwise lack of training as the main cause of inaccuracy or non-equivalence in their rendition of the source-language (SL) speaker’s message into the target language (TL). Drawing on the authentic data of nine criminal trials from the courts of Hong Kong, this study demonstrates judges’ intervention in witness examination as a cause of omissions in court interpreting. This study is situated in the bilingual Hong Kong courtroom, where the interpreting service in a trial conducted in English is a sine qua non due to the linguistic dichotomy between English-speaking legal professionals and Cantonese-speaking lay litigants. The access of non-English-speaking (NES) participants to utterances produced in English in witness examination is made possible by the interpretation provided in the consecutive mode in open court. This study illustrates how a judge’s intervention in the proceedings can lead to omissions and/or a change from the consecutive mode to the more restrictive chuchotage mode of interpreting and discusses how this may impact on the participation status of NES court actors and potentially compromise the administration of justice. It concludes by suggesting solutions to the problems identified.